Exploring the Therapeutic Potential of Shallot Extract in Gastritis - Vivi Shofia; Fahmi Dimas Abdul Azis; Adek Bela Anggraeni; Hamida Nurlaila (JURNAL FARMASI DAN MAKANAN, 2025)
Gastritis, commonly known as stomach ulcers, is a widespread condition caused by poor eating habits, certain foods, infections, and NSAID use. In Indonesia, WHO reports a 40.8% prevalence, making it a major health issue. This study aimed to evaluate the effects of ethanol-extracted shallot (Allium sp.) skin and bulb on malondialdehyde (MDA) levels and gastric histopathology in rats with indomethacin-induced gastritis. Gastritis was induced in Rattus norvegicus, followed by treatment with shallot extract. MDA levels and tissue damage were then analyzed using Hematoxylin-Eosin staining. Results showed a significant reduction in MDA levels, especially with 200 mg/kg body weight of shallot skin extract, which achieved a 92.18% decrease. Histopathological analysis revealed notable improvements in gastric tissue, with reduced ulceration and inflammation. The findings support the potential of shallot extract in lowering oxidative stress and repairing gastric damage, suggesting its promise as an alternative therapy for gastritis.